A randomised controlled trial of sodium citrate spray for non‐conductive olfactory disorders. (17th April 2017) - Philpott, C.M.; Erskine, S.E.; Clark, A.; Leeper, A.; Salam, M.; Sharma, R.; Murty, G.E.; Hummel, T.
Abstract : Objectives: Previous research has suggested that sodium citrate improves hyposmia by decreasing mucus calcium levels in the nose. This study aimed to confirm or refute this effect in a single application and assess potential side‐effects. Design: Study design was a randomised double‐blind controlled trial of sodium citrate nasal spray (intervention) vs sterile water (control). Fifty‐five patients with non‐conductive olfactory loss were randomised to receive the intervention or placebo. Setting: Tertiary care clinic. Main outcome measures: The primary outcome measure was improvement in measured olfactory thresholds for phenyl ethyl alcohol (PEA) over 2 hours. Other outcome measures assessed were improvement in olfactory thresholds in 1‐butanol, eucalyptol and acetic acid; number of responders with a clinically relevant response in each arm; and adverse effects. Results: A significant effect was seen in the intervention arm for PEA and for 1‐butanol and eucalyptol when compared to the control arm ( P <.05); 32% of the intervention arm responded in terms of improved sensitivity towards some of the odours. Minor adverse effects noted included sore throat, nasal paraesthesia, slight rhinorrhoea and itching. The duration of effect of the citrate is transient, peaking at 30‐60 minutes after application. Conclusions: Sodium citrate yields some potential as a treatment for non‐conductive olfactory loss; however, these findings require corroboration in further clinical trials looking at longer term regular use of the spray as a viable therapeutic option for patients where it would be applied at frequent intervals such as before mealtimes.